Market Performance: Market Orientation and Entrepreneurship Orientation with Innovation - Achmad Firdiansjah, Harianto Respati, Amin Kuncoro (International Journal of Advanced Science and Technology, 2020)
This research aims to examine market orientation and entrepreneurship orientation toward market performance through innovation.  This research applies an exploratory-descriptive design. The population and the sample consisted of small and medium enterprises (SMEs) in Kudus municipality with a total of 185 respondents. The analysis data technique is quantitative descriptive. The research data sources are primary and secondary data. The findings explain that market orientation positively and significantly influences the employees' performances. The entrepreneurship positively and significantly influences market performance. Innovation could mediate market and entrepreneurship orientations with market performance. The research test results explain a partial mediation.